2024
DOI: 10.3390/separations11050150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the SPIRITAS: A Disposable Sampling Setup for Volatile Organic Compound Collection and Analysis

David J. Mager,
Yoni E. van Dijk,
Özgü Varan
et al.

Abstract: Analyzing exhaled breath for volatile organic compounds (VOCs) using thermal desorption–gas chromatography–mass spectrometry (TD-GC-MS) offers a non-invasive diagnostic approach for various diseases. Despite its promise, the method faces challenges like sampling heterogeneity and high costs. Following the European Respiratory Society’s advocacy for methodological standardization, we developed the SPIRITAS (Standardized Product for Inexpensive Respiratory InvesTigation: A breath Sampler), a low-cost, disposable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, contamination from background VOCs can be easily introduced during breath collection and sample storage depending on the choice of offline analysis methodology. Tedlar®, Nalophan ® , and Mylar ® bags are a common method of breath collection for offline techniques, whereby participants in breath studies exhale and fill the bags (Ghimenti et al, 2015 ; Mager et al, 2024 ; Sola-Martínez et al, 2023 ). While inexpensive, disposable, and easy to use, studies have shown that these bags can be a source of contaminating compounds like N,N-dimethylacetamide and phenol, and may leak, especially during handling (Beauchamp et al, 2008 ; Ghimenti et al, 2015 ; Groves & Zellers, 1996 ; Harshman et al, 2020 ; Steeghs et al, 2007 ; Sulyok et al, 2001 ).…”
Section: Breath Collection Methodologymentioning
confidence: 99%
“…However, contamination from background VOCs can be easily introduced during breath collection and sample storage depending on the choice of offline analysis methodology. Tedlar®, Nalophan ® , and Mylar ® bags are a common method of breath collection for offline techniques, whereby participants in breath studies exhale and fill the bags (Ghimenti et al, 2015 ; Mager et al, 2024 ; Sola-Martínez et al, 2023 ). While inexpensive, disposable, and easy to use, studies have shown that these bags can be a source of contaminating compounds like N,N-dimethylacetamide and phenol, and may leak, especially during handling (Beauchamp et al, 2008 ; Ghimenti et al, 2015 ; Groves & Zellers, 1996 ; Harshman et al, 2020 ; Steeghs et al, 2007 ; Sulyok et al, 2001 ).…”
Section: Breath Collection Methodologymentioning
confidence: 99%